Peran Budaya Organisasi dan Disiplin Kerja dalam Membentuk Workplace Deviant Behavior pada Perusahaan Manufaktur - Sekar Arum Pratiwi; Ika Korika Swasti; Daisy Marthina Rosyanti (Jurnal Riset Pendidikan Ekonomi, 2026)
This study aims to analyze the role of organizational culture and work discipline on deviant behavior in the workplace at a flexible packaging materials manufacturing company located in Sidoarjo Regency. This study employs a quantitative approach using a survey method. The sample consisted of 86 respondents, selected through purposive sampling based on the criterion of permanent employees who had been working for at least one year. Data were collected via a questionnaire using a Likert scale and document analysis, then analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that organizational culture plays a significant role in reducing the occurrence of deviant behavior in the workplace, as well-internalized values and norms can shape employee behavior in a more positive manner. On the other hand, work discipline is also involved in creating order, although its impact has not yet shown a significant influence. A strong organizational culture and consistent enforcement of work discipline can reduce the potential for deviant behavior, thereby enabling companies to maintain operational stability and enhance long-term effectiveness. This study also fills a gap in the literature, as most previous research has focused more on the influence of organizational culture and work discipline on performance rather than on deviant behavior in the workplace. These findings contribute theoretically by expanding our understanding of the factors influencing deviant behavior in the workplace, particularly within the manufacturing sector in Indonesia. Practically, the results of this study can serve as a guide for company management in developing more effective strategies to strengthen cultural values and work discipline systems, thereby reducing the risk of deviant behavior and improving work productivity.